A biomimetic ZIF nanoagent for synergistic regulation of glutamine metabolism and intracellular acidosis of cancer. Issue 10 (11th January 2022) - Wang, Mengzhen; Lu, Fei; Li, Na; Pan, Wei; Tang, Bo
Abstract : A homotypic cancer cell membrane camouflaged ZIF-based nanoagent was developed to improve anticancer efficiency through synergistic metabolism regulation and acidosis aggravation. Abstract : A homotypic cancer cell membrane camouflaged zeolitic imidazolate framework (ZIF)-based nanoagent with co-loading of two inhibitors was developed, which could suppress the efflux of protons to induce intracellular acidic stress and down-regulate glutamine metabolism to reduce the energy supply. As a compensation, glycometabolism would be upregulated with simultaneous production of large amounts of lactic acid, which could in turn aggravate the acidosis and further realize a synergetic cancer treatment.